Collaborative Governance in the Effort to Prevent the Criminal Action of the Financing of Terrorism Through Freezing of Individual and Entity Assets - Guntur Wijaya Kesuma; Surya Nita; Zora A. Sukabdi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
UN Security Council Resolutions 1267 (1999) and 1373 (2001), call on all countries in the world to provide financial sanctions against Al-Qaeda and the Taliban, including citizens of every country affiliated with and assisting Al-Qaeda and the Taliban. In 2012, the FATF once more classified Indonesia as a "Non-cooperative Countries and Territories (NCCTs)", this time in relation to the handling of criminal acts of terrorism financing, because it determined that Indonesia's regulations for handling terrorism financing did not meet the international standards outlined in the FATF's recommendations, thereby placing Indonesia at a high risk of financing terrorism, which has an effect on the Indonesian economy because all countries are at risk of financing terrorism. Based on the data obtained, this study intends to find the obstacles faced by the Indonesian government and provide input on how to build collaboration between the government and other elements in efforts to prevent criminal acts of terrorism financing through freezing the assets of individuals and entities listed on the List of Suspected Terrorists and Terrorist Organizations (DTTOT), as well as Indonesia's efforts to become a permanent member of the FATF in 2023, as per Recommendation 6 of the FATF.